2016
DOI: 10.1080/09593330.2016.1231223
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of polyamide thin-film nanocomposite membranes with enhanced surface charge for nitrate ion removal from water resources

Abstract: Exclusion due to membrane surface charge is considered as one of the main separation mechanisms occurring in charged membranes, which can be varied through various approaches to affect membrane rejection performance. In this study, thin-film composite (TFC) polyamide (PA) membranes were fabricated via interfacial polymerization of m-phenylenediamine (m-PDA) and 2,4-diaminobenzene sulfonic acid with trimesoyl chloride (TMC) on a polysulfone sub-layer. The ability of the prepared membrane to remove nitrate ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, the membrane properties can be improved by modifying the thin layer using hydrophilic nanoparticles . The nanoparticles that have been previously used for TFN membrane synthesis include zeolite , titanium dioxide (TiO 2 ) , , graphene oxide (GO) , , silver , silica , and metal‐organic frameworks (MOFs) , . Previous studies showed that the incorporation of nanoparticles generally help to boost up the water permeation flux, mainly attributed to alteration of membrane surface hydrophilicity , .…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the membrane properties can be improved by modifying the thin layer using hydrophilic nanoparticles . The nanoparticles that have been previously used for TFN membrane synthesis include zeolite , titanium dioxide (TiO 2 ) , , graphene oxide (GO) , , silver , silica , and metal‐organic frameworks (MOFs) , . Previous studies showed that the incorporation of nanoparticles generally help to boost up the water permeation flux, mainly attributed to alteration of membrane surface hydrophilicity , .…”
Section: Introductionsupporting
confidence: 88%
“…Previous studies showed that the incorporation of nanoparticles generally help to boost up the water permeation flux, mainly attributed to alteration of membrane surface hydrophilicity , . Other positive features of adding nanomaterials into the matrix of composite membranes involve increased solute rejection rates , better antibacterial properties , and stronger resistance against organic/inorganic fouling .…”
Section: Introductionmentioning
confidence: 99%
“…e model uses a basic 3-layer topology, namely, the input layer, the hidden layer, and the output layer. e input layer has 7 nodes, which represent 7 relevant factors that affect the task price [16,40]. Concept drift refers to the phenomenon that the concepts implicit in the data change over time.…”
Section: Research On English Film and Television Resource Informationmentioning
confidence: 99%
“…In the film industry, through the analysis of massive amounts of film and television data, the application system can effectively push the works that users may like. Recently, some film production companies have tried to use the results of data analysis to design castings and scripts, and their works have been very successful [11][12][13][14][15][16][17][18]. Movie data contains a wealth of information, but the current mining and analysis work for it often only focuses on specific information, which affects the integrity of the results to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid NF membranes are also of interest due to their performance under suboptimal conditions. Various polymers, such as po lyethersulfone (Maximous et al, 2009), polydimethylsiloxane (Yousefi et al, 2017), polyvinylidene fluoride (Dong et al, 2013), and polysulfone (Ghaee et al, 2017) were tested as top layer materials for hybrid membranes. The use of polymers for obtaining hybrid NF membranes makes it possible to change pore sizes, chemical properties, and charges of membrane surfaces.…”
Section: Filtrationmentioning
confidence: 99%